Prognostic value of alkaline phosphatase in hormone-sensitive prostate cancer: a systematic review and meta-analysis - Mori, Keiichiro (Int J Clin Oncol, 2019)
PURPOSE: To assess the prognostic value of alkaline phosphatase in patients with hormone-sensitive prostate cancer. METHODS: A systematic review and meta-analysis was performed using the PUBMED, Web of Science, Cochrane Library, and Scopus in April 2019 according to the Preferred Reporting Items for Systematic Review and Meta-analysis statement. Studies were deemed eligible if they compared hormone-sensitive prostate cancer patients with high vs. low alkaline phosphatase to determine its predictive value for overall survival, cancer-specific survival, and progression-free survival. We performed a formal meta-analysis of these outcomes. RESULTS: 42 articles with 7938 patients were included in the systematic review and 28 studies with 5849 patients for the qualitative assessment. High alkaline phosphatase was associated with worse overall survival (pooled HR 1.72; 95% CI 1.37−2.14) and progression-free survival (pooled HR 1.30; 95% CI 1.10−1.54). In subgroup analyses of patients with “high-volume” and “low-volume”, alkaline phosphatase was associated with the overall survival (pooled HR 1.41; 95% CI 1.21−1.64 and pooled HR 1.64; 95% CI, 1.06−2.52, respectively). CONCLUSIONS: In this meta-analysis, elevated serum levels of alkaline phosphatase were associated with an increased risk of overall mortality and disease progression in patients with hormone-sensitive prostate cancer. In contrast, those were not associated with an increased risk of cancer-specific mortality. Alkaline phosphatase was independently associated with overall survival in both patients with “high-volume” and “low-volume” hormone-sensitive prostate cancer. Alkaline phosphatase may be useful for being integrated into prognostic tools that help guide treatment strategy, thereby facilitating the shared decision making process.